PENGARUH NPK MAJEMUK TERHADAP PELINDIAN N-TOTAL DAN C-ORGANIK PADA TANAH PODSOLIK MERAH KUNING DAN TANAH SULFAT MASAM - Muhammad Saleh; Basuki Basuki; Sustiyah Sustiyah; Rolland Agustin Umbing; Wuni Oktavia (AgriPeat, 2022)
The research aims to determine the effect of leaching on N-total and C-organic on podzolic soils and acid sulphate soils. This research was conducted for 6 weeks from March until April 2020, housed in the Laboratory of the Department of Agriculture, Faculty of Agriculture, University of Palangka Raya. This research used Complete Random Design (CRD) single factor. There are 6 treatments namely P1 = NPK fertilizer = 0 kg.ha-1 on Podzolic Red Yellow (PRY); P2 = NPK fertilizer = 150 kg.ha-1 on Podzolic Red Yellow (PRY) ; P3 = NPK fertilizer = 300 kg.ha-1 on Podzolic Red Yellow (PRY); P4 = NPK fertilizer = 0 kg.ha-1 on Acid Sulphate Soils (ASS); P5 = NPK fertilizer = 150 kg.ha-1 on id Sulphate Soils (ASS); P6 = NPK fertilizer = 300 kg.ha-1 on Sulphate Soils (ASS);. Each treatment was repeated 3 times. The measured variable is the content of N-total, and C-organic in soil and water leaching. Data were analyzed with analysis of variance on the level of alpha = 0.05 and alpha = 0,01. If there is real effect in treatment, The result of HRD (Honest Real Different) level of alpha = 0.05. The results of research showed the higher dose of NPK fertilizer compound given cause increased content of N-total, and C-organic on a red-yellow podzolic soil and acid sulfate soil before leaching and after leaching. The dose of NPP fertilizer Compound that high will increase the content of N-total, and C-organic dissolved in water leaching red yellow podzolic soil and acid sulphate soils.